A variação dos pronomes de segunda pessoa na mesorregião mineira Campo das Vertentes - Suelen Cristina da Silva (2022)
Under the light of Variational Sociolinguistics, the present study aims at investigating the variation phenomenon among second person pronouns tu, você, ocê, and cê (you) in Brazilian Portuguese, in three cities in the State of Minas Gerais, Brazil, based in Campos das Vertentes mesoregion, as follows: Alfredo Vasconcelos, Barbacena and Ressaquinha. Such proposal relies not only on the need for further studies on the issue in the state, but also on trend in the use of the tu form in such region. The corpus of this research is comprised of two samples: sociolinguistic interviews as well as perception and production tests. With regard to the first sample, 54 sociolinguistic interviews were to be used, encompassing a total of 18 informants per city. In turn, in the perception and production tests, 36 tests have been carried out (12 per municipality). In order to select participants for both samples, the extralinguistic variables addressed by his study were taken into account, i.e., gender (male and female), and age group (18 to 30 years old, 31 to 50 years old, 51 years old or more). The results show that, in the cities of Alfredo Vasconcelos and Barbacena, there is predominant use of the form cê and, in the region of Ressaquinha, the pronoun tu seems to be more recurrent among speakers. In relation to the multivariational analysis of data, in terms of specific data of result approximation in the three regions analyzed, one may note that: a) the variable of syntactic context favors the use of cê; b) the variable of formal parallelism, variable which was selected solely in Alfredo Vasconcelos and Ressaquinha, shows that the variant tu was favored when employed with the 2P paradigm in both regions; c) the variable of type of verb, which points out that the form tu is used alongside action verbs and the pronouns você and ocê are favored when used in contexts with verba dicendi and with stative verbs; d) the variable of type of discourse shows that the form tu is favored when used in contexts of direct speech and the forms você, ocê and cê tend to occur in generic speeches; e) the variable of extralinguistic factors of gender shows that, in Barbacena and Ressaquinha, the pronoun tu is related to the male gender and, in Alfredo Vasconcelos, such pronominal element is favored in female speeches, and f) the variable of age demonstrates predominance of the form tu in the speeches of younger individuals (aged 18 to 31) as well as favoring of você among elder speakers (51-year-olds or more) and the pronoun ocê is more productive in the age gap of the average individuals (aged 31 to 50). With regard to the sample of perception tests and production, the results of the perception test show that, in the semetric relationship (among friends), speakers from Alfredo de Vasconcelos and Barbacena opted for the form você in interactions among friends whereas interviewees from Ressaquinha are incled to use the pronoun tu. When it comes to ascendant asymmetric relationships, the title o/a senhor(a) is predominant in the choice of speakers from the three cities analyzed. Regarding the production test, the data show that interviewees from Alfredo Vasconcelos and Barbacena tend to choose combinations with the pronoun você either with parallel forms (with the 3P paradigm) or with non-parallel forms (with the 2P paradigm), while participants from Ressaquinha are more likely to use the variant tu as well as the forms of the 2P paradigm. Regarding preposition complements, it is noteworthy that pra tu is preferred among interviewees and, in Alfredo Vasconcelos and Barbacena, the majority of participants opted for the complement pra você.